The Effects of Using Electronic Maps While Driving on The Driver Performance - Lovely Lady; Ani Umyati (International Journal of Technology, 2023)
The development of information technology has provided electronic maps (e-maps) via mobile phones that help drivers find the travel destinations, but using mobile phone also can disturb the driver’s concentration. The aims of the research is to analyze the effects of using e-maps while driving on driver performance. The respondents were private car drivers, and as many as 325 respondents filled out the questionnaire. The drivers answered the questions about their experience using e-map while driving and particular behavior. As many as 45.54% of drivers involved in undesired circumstances such as changing lanes or slowing down suddenly and 20.00% involved in a near-miss accident. Meanwhile 39.94% of drivers stated to never be involved in any adverse event. The group of drivers who have aberrant behavior was involved in adverse event more often than the group of drivers who obey the rules (t-test, a=0.000). Regression analysis is performed to analyze the correlation between four types of aberrant behavior and the driver violations, there were moderate correlations between the research variables. The use of e-maps do not increase traffic violations when applied by obedient traffic rule drivers, but it does increase when applied aberrant behavior drivers.